Earnings, risk-taking, and capital accumulation in small and large community banks - Balla, Eliana; Rose, Morgan J. (Journal of Banking & Finance, 2019)
We examine the relationships between ownership structure and both earnings and risk-taking among community banks before, during, and after the US financial crisis. We find that publicly-held small community banks had lower earnings than privately-held ones before the recession, but had higher earnings during and after the recession. Publicly-held small community banks exhibited similar risk-taking to privately-held ones before and during the recession, but greater risk-taking after. We also find that publicly-held small community banks de-risked more slowly than privately-held ones following the recession. Large community banks, on the other hand, show no consistent relationship between ownership structure and earnings, and a strong cyclical relationship between ownership structure and risk-taking. These findings expand our understanding of how community bank performance and capital accumulation behaves through different cyclical periods, and how ownership structure affects that behavior.